Dimensions That Integrate The Health Variable “Lifestyles” (The Review of Diabetic Studies, 2024)
This essay explores the integration of health-related lifestyles within the framework of the salutogenic and health promotion models, emphasizing the need to move beyond the biomedical approach traditionally centered on disease. It analyzes the conceptual foundations and dimensions that constitute healthy lifestyles according to the Colombian Ministry of Health and Social Protection, including physical activity, food and nutritional security, healthy work environment, handwashing, healthy weight, tobacco prevention, and sensory health (oral, visual, and auditory). Furthermore, it relates these dimensions to Nola Pender’s Health Promotion Model, highlighting the importance of health responsibility, interpersonal relationships, spiritual growth, and stress management as determinants of individual and collective well-being. The study concludes that promoting healthy lifestyles requires integrating physical, emotional, social, and spiritual dimensions through coordinated and intersectoral actions. This integration enables the construction of equitable, resilient, and health-conscious societies, fostering autonomy and informed decision-making regarding health.